Pemanfaatan Limbah Anorganik oleh Kelompok Ibu Rumah Tangga di Kabupaten Pangkep - Ida suryani; Muhammad Amir (DEDIKASI, 2018)
This Community Partnership Program (PKM) aims to utilize inorganic waste, especially plastic, intohandicraft products with good economic value. This program is conducted on March to October 2018 inPa'bundukang village, Pangkaje'ne district of Pangkep Regency, with Lotus Housewives Group and AsokaHousewives Group. The activity in this program consists of counseling, training, mentoring and demonstration. Theresults show that the housewives' creativity and the community in general in reusing from plastic waste increased.Through counseling, training and demonstration on how to use inorganic waste creatively, the inorganic wastematerial can be made into various kinds of interesting and economical handicraft products to increase the income ofhousewives.